Non-Invasive Skin Imaging Assessment of Human Stress During Head-Down Bed Rest Using a Portable Handheld Two-Photon Microscope - Wang, Junjie; Zhen, Zhen; Wang, Yanqing; Wu, Runlong; Hu, Yanhui; Fu, Qiang; Li, Yongzhi; Xin, Bingmu; Song, Jinping; Li, Jianwei; Ren, Yafei; Feng, Lishuang; et al. (Frontiers in Physiology, 2022)
Spaceflight presents a series of physiological and pathological challenges to astronauts resulting from ionizing radiation, microgravity, isolation, and other spaceflight hazards. These risks cause a series of aging-related diseases associated with increased oxidative stress and mitochondria dysfunction. The skin contains many autofluorescent substances, such as nicotinamide adenine dinucleotide phosphate (NAD(P)H), keratin, melanin, elastin, and collagen, which reflect physiological and pathological changes in vivo. In this study, we used a portable handheld two-photon microscope to conduct high-resolution in vivo skin imaging on volunteers during 15 days of head-down bed rest. The two-photon microscope, equipped with a flexible handheld scanning head, was used to measure two-photon excited fluorescence (TPEF) and second harmonic generation (SHG) images of the left forearm, left front chest, and forehead of volunteers. Changes in TPEF, SHG, and the extended SHG-to-AF(TPEF) aging index of the dermis (SAAID) were measured. It was found that TPEF intensity increased during bed rest and was restored to normal levels after recovery. Meanwhile, SHG increased slightly during bed rest, and the skin aging index increased. Moreover, we found the skin TPEF signals of the left forearm were significantly negatively associated with the oxidative stress marker malondialdehyde (MDA) and DNA damage marker 8-hydroxy-2′-desoxyguanosine (8-OHdG) values of subjects during head-down bed rest. Meanwhile, the SHG signals were also significantly negatively correlated with MDA and 8-OHDG. A significant negative correlation between the extended SAAID of the left chest and serum antioxidant superoxide dismutase (SOD) levels was also found. These results demonstrate that skin autofluorescence signals can reflect changes in human oxidant status. This study provides evidence for in-orbit monitoring of changes in human stress using a portable handheld two-photon microscope for skin imaging.